Three categories of similarities between the placenta and cancer that can aid cancer treatment: Cells, the microenvironment, and metabolites - Pang, Huiyuan; Lei, Di; Guo, Yuping; Yu, Ying; Liu, Tingting; Liu, Yujie; Chen, Tingting; Fan, Cuifang (Frontiers in Oncology, 2022)
Cancer is one of the most harmful diseases, while pregnancy is a common condition of females. Placenta is the most important organ for fetal growth, which has not been fully understand. It’s well known that placenta and solid tumor have some similar biological behaviors. What’s more, decidua, the microenvironment of placenta, and metabolism all undergo adaptive shift for healthy pregnancy. Interestingly, decidua and the tumor microenvironment (TME); metabolism changes during pregnancy and cancer cachexia all have underlying links. However, whether the close link between pregnancy and cancer can bring some new ideas to treat cancer is still unclear. So, in this review we note that pregnancy may offer clues to treat cancer related to three categories: from cell perspective, through the shared development process of the placenta and cancer; from microenvironment perspective, though the shared features of the decidua and TME; and from metabolism perspective, through shared metabolites changes during pregnancy and cancer cachexia. Firstly, comparing gene mutations of both placenta and cancer, which is the underlying mechanism of many similar biological behaviors, helps us understand the origin of cancer and find the key factors to restore tumorigenesis. Secondly, exploring how decidua affect placenta development and similarities of decidua and TME is helpful to reshape TME, then to inhibit cancer. Thirdly, we also illustrate the possibility that the altered metabolites during pregnancy may reverse cancer cachexia. So, some key molecules changed in circulation of pregnancy may help relieve cachexia and make survival with cancer realized.